Sasaq Local Wisdom-Based ELT Materials in Improving Intercultural Competences and Speaking Skills as Pancasila Learners’ Profiles - Haerazi, Haerazi; Reformana, Gusti Bagus Adri Yogha; Irawan, Lalu Ari (Journal of English Education and Teaching, 2024)
This study investigates the effectiveness of English Language Teaching (ELT) materials incorporating Sasak local wisdom in enhancing learners' intercultural competence and speaking skills, aligning with the Pancasila learners' profiles. The research adopts a mixed-method concurrent embedded design, combining both quantitative and qualitative approaches. The experimental aspect utilizes a pretest-posttest control group design, where learners' speaking skills and intercultural competence are assessed before and after the implementation of the local wisdom-based materials. Quantitative data were analyzed using statistical methods, while qualitative data from learner feedback and observations were analyzed thematically. The findings reveal that integrating Sasak local wisdom into ELT materials significantly enhances learners’ communication skills, particularly in speaking classes. The cultural relevance of the materials engages students more deeply, allowing them to relate to the content and express themselves more fluently. Additionally, learners demonstrate improved intercultural competence, gaining a broader understanding of both local and global cultures. Learner feedback highlights the positive impact of cultural integration, with many students expressing that the materials’ relatability fosters a more enjoyable and meaningful learning experience. The implications of these findings suggest that local culture-based ELT materials should be more widely incorporated into EFL curricula to create engaging, culturally relevant learning environments. This approach not only improves language proficiency but also fosters intercultural awareness, preparing learners to navigate cross-cultural communication more effectively. Integrating local cultural elements in the curriculum enriches learners’ language learning experience and promotes a more inclusive, globally informed perspective.